Analysis Creative Thinking Ability of Student’s on the Topic of Momentum and Impulse in Senior High School - I Putu Yogi Setia Permana; Parno; Endang Purwaningsih; Marlina Ali (Postgraduate, University of Mataram, 2023)
The capacity for creative thought is one of the skills that people in the 21st century need to have. Creative thinking ability refers to a person's ability to use their way of thinking to generate new ideas. Teachers must choose the best teaching strategy to provide pupils the chance to be creative. This study seeks to give a general picture of students' capacity for creatively thought about momentum and impulse. This study is quantitative and descriptive. As the research subjects, 57 students from classes XI MIPA 1 and XI MIPA 2 of SMA Negeri 1 Menggala participated in the study. The sample for this study was chosen using the cluster random sampling technique. A four-essay creative thinking exam with a reliability score of 0.610 and measures of fluency, flexibility, originality, and elaboration. The study's findings demonstrate that student have a considerable ability for creative thought. The indicator of fluency in thinking received the highest score of 54.67%, the indicator of flexibility of thinking was 47.2%, the indicator of originality was 34.93%, and the indicator of elaboration received the lowest proportion, 28.27%. This shows that students have the ability to develop different ideas in different ways, but they still have difficulty explaining these ideas.